Pegylated recombinant human granulocyte colony-stimulating factor enhances radiotherapy completion and safety in concurrent chemoradiotherapy for cervical cancer: a retrospective analysis - Zhao, Lingli; Zhai, Yanhong; Meng, Luhong; Ren, Yajuan; Liu, Nannan; Xing, Xuejiao; Wen, Xin; Niu, Gaoli (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the impact of pegylated recombinant human granulocyte colony-stimulating factor (PEG-rhG-CSF) on radiotherapy completion rates and safety in cervical cancer patients undergoing concurrent chemoradiotherapy.MethodsThis retrospective study analyzed 60 cervical cancer patients treated at the researchers’ hospital between October 2021 and October 2024. The patients were divided into two groups: the PEG-rhG-CSF group (n = 30), which received pegylated recombinant human granulocyte colony-stimulating factor (PEG-rhG-CSF), and the non-PEG-rhG-CSF group (n = 30), which received recombinant human granulocyte colony-stimulating factor (rhG-CSF). Key outcomes, including radiotherapy completion time, hematological toxicity, and non-hematological adverse events, were compared between the two groups.ResultsThe results demonstrated that 83.33% of patients in the PEG-rhG-CSF group completed radiotherapy within 8 weeks, compared to 51.72% in the non-PEG-rhG-CSF group. The time to bone marrow suppression was significantly longer in the PEG-rhG-CSF group (4.93 ± 0.22 weeks) than in the non-PEG-rhG-CSF group (4.07 ± 0.22 weeks). Additionally, the lowest white blood cell (WBC) count in the PEG-rhG-CSF group was 2.46 ± 0.13 × 109/L, which was significantly higher than 2.04 ± 0.13 × 109/L in the non-PEG-rhG-CSF group (P = 0.025). The incidence of grade 3/4 neutropenia was significantly lower in the PEG-rhG-CSF group (16.67%) compared to the non-PEG-rhG-CSF group (56.67%) (P = 0.003). Furthermore, no febrile neutropenia (FN) cases were observed in the PEG-rhG-CSF group, whereas six cases occurred in the non-PEG-rhG-CSF group (P < 0.05). Non-hematologic adverse reactions were comparable between the two groups, and the bone pain associated with PEG-rhG-CSF was tolerable.ConclusionThe study demonstrates that PEG-rhG-CSF has significantly improved radiotherapy completion rates and reduced the incidence of grade 3/4 leukopenia and neutropenia in cervical cancer patients undergoing concurrent chemoradiotherapy. Additionally, PEG-rhG-CSF has exhibited a favorable safety profile, with manageable adverse effects, making it a promising supportive treatment option in this setting.SynopsisThis study explores the application of PEG-rhG-CSF in concurrent chemoradiotherapy for cervical cancer. A retrospective analysis evaluates its effectiveness in helping patients’ complete radiotherapy on time, reducing hematologic toxicity, and ensuring safety.